Modified graphene oxide, preparation method of modified graphene oxide, modified graphene oxide coating solution and application of modified graphene oxide coating solution
By grafting nanotitanium dioxide and polydopamine on the surface of graphene oxide, the modified graphene oxide is formed, which solves the problem of insufficient corrosion resistance of graphene oxide and achieves higher corrosion resistance and thermal stability.
Patent Information
- Application Number
- CN202411726148.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-11
AI Technical Summary
Existing graphene oxide is insufficient in corrosion resistance in more stringent corrosion-resistant environments, making it difficult to meet higher corrosion-resistant needs.
By grafting nanotitanium dioxide and polydopamine onto the surface of graphene oxide, modified graphene oxide is formed, which improves its density and barrier properties.
The corrosion resistance and thermal stability of modified graphene oxide are significantly improved, and the coordinated optimization of corrosion resistance and thermal stability is achieved.
Smart Images

Figure CN119592105A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and specifically relates to modified graphene and a preparation method thereof, a modified graphene coating solution and applications thereof. Background Art
[0002] Graphene oxide (GO) is a commonly used anti-corrosion material. It can be directly used as a coating for the anti-corrosion of metal materials, and can also be added to resin materials to improve the corrosion resistance of resin coatings. Graphene oxide has a thin two-dimensional structure, which enables it to form a dense coating that effectively blocks the penetration of corrosive media (such as water, oxygen, ions, etc.); when graphene oxide is added as a filler to organic coatings such as resin materials, it can fill the micropores and defects in the coating, further improving the density and barrier properties of the coating. Graphene oxide has high chemical stability and inertness, is not easy to react chemically with corrosive media, and can maintain stable performance in harsh corrosive environments, thereby extending the service life of the coating. However, when faced with more stringent anti-corrosion requirements, the corrosion resistance of graphene oxide still needs to be improved.
[0003] Based on this, it is necessary to provide a modified graphene oxide and a preparation method thereof, a modified graphene oxide coating solution and an application thereof, so as to alleviate or solve the above problems. Summary of the invention
[0004] The invention aims to solve the technical problem that the modified graphene oxide in the above-mentioned common technology has poor corrosion resistance. The present invention provides a modified graphene oxide, comprising graphene oxide, nano-titanium dioxide and a polydopamine film. The graphene oxide has a wrinkled layered structure, the polydopamine film is wrapped on the surface of the graphene oxide, and the nano-titanium dioxide is uniformly dispersed on the surface of the graphene oxide.
[0005] Furthermore, the corrosion current density of the modified graphene oxide is 1.04×10 -5 ~2.33×10 -5 A / cm 2 .
[0006] Furthermore, the functional groups on the surface of the modified graphene oxide include -OH, C=N, C=C, COC, Ti-O-Ti, and Ti-OC.
[0007] The present invention provides a method for preparing the modified graphene oxide as described in any one of the above, comprising the steps of:
[0008] The graphene oxide is dispersed to obtain a graphene oxide dispersion;
[0009] The graphene oxide dispersion is mixed with dopamine hydrochloride and nano-titanium dioxide to obtain a graphene oxide mixture, and the graphene oxide mixture is subjected to stirring treatment and solid-liquid separation in sequence, and the solid product is collected to obtain the modified graphene oxide, wherein the mass ratio of the graphene oxide to the dopamine hydrochloride and the nano-titanium dioxide is 1:0.25-2.0:0.25-2.0.
[0010] Furthermore, the mass ratio of the graphene oxide to the dopamine hydrochloride and the nano-titanium dioxide is 1:1:0.5-1.0.
[0011] Furthermore, the dispersion treatment includes the steps of placing the graphene oxide in deionized water and ultrasonically dispersing for 30 to 60 minutes to obtain the graphene dispersion.
[0012] Furthermore, the stirring treatment includes: ultrasonicating the graphene oxide mixture for 30 to 60 minutes, and then stirring at a rotation speed of 300 to 400 for 20 to 30 hours.
[0013] Furthermore, the step of subjecting the graphene oxide mixture to stirring treatment and solid-liquid separation in sequence, collecting the solid product, and obtaining the modified graphene oxide also includes washing the solid product alternately with deionized water and ethanol for 2 to 5 times, and drying the solid product to obtain the modified graphene oxide, wherein the drying treatment temperature is 50 to 70° C., and the drying treatment time is 10 to 20 hours.
[0014] The present invention provides an application of the modified graphene oxide as described in any one of the above items in metal corrosion protection.
[0015] The present invention provides a modified graphene oxide coating solution, comprising the modified graphene oxide as described in any one of the above items and a binder.
[0016] Compared with the prior art, the present invention has at least the following advantages:
[0017] The present invention provides a modified graphene oxide, such as Figure 2As shown in (d), graphene oxide presents a wrinkled layered structure, nano-titanium dioxide and dopamine are grafted on the surface of the graphene oxide, wherein dopamine, as an organic substance with self-polymerization characteristics, can form a polydopamine film with super strong adhesion, greatly improving the binding ability of nano-titanium dioxide particles and graphene oxide, making nano-TiO2 dispersed evenly on the GO surface and preventing agglomeration. The incorporation of nano-TiO2, on the one hand, generates a passivation film on the surface of graphene oxide, improves the compactness and barrier properties of the modified graphene oxide, and effectively slows down the corrosion process. On the other hand, nano-TiO2 and the like can form a bond with oxygen-containing functional groups on the surface of GO, reduce the π-π stacking and agglomeration phenomenon between GO sheets, improve the corrosion resistance of GO, and also enhance its mechanical strength and thermal stability, thereby achieving the synergistic optimization of the corrosion resistance and thermal stability of the modified graphene oxide.
[0018] In comparison, in commonly used technologies, the GO surface contains a large number of oxygen-containing functional groups, which lead to strong interactions between GO nanosheets, such as π-π stacking, hydrogen bonding and van der Waals forces. The above forces cause the GO nanosheets to agglomerate, thereby affecting the uniformity of GO dispersion and reducing corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0020] Figure 1 The scanning electron microscope (SEM) of GO, GO-DA, GO-TiO2 and DA@GO-TiO2 in the analysis example 1 of the present invention is shown in FIG. Figure 1 (a) Figure 1 (b) Electron micrographs of graphene oxide before and after dopamine treatment, i.e., GO and GO-DA; Figure 1 (c) and (d) are electron micrographs of GO-TiO2 and DA@GO-TiO2, respectively.
[0021] Figure 2 This is a transmission electron microscope (TEM) image of GO and DA@GO-TiO2 in the analysis example 1 of the present invention, wherein: Figure 2 (a) is the TEM image of GO. Figure 2 (b)-(d) are TEM images of DA@GO-TiO2 at different scales;
[0022] Figure 3XRD patterns of GO, GO-DA, GO-TiO2 and DA@GO-TiO2 in analysis example 2 of the present invention.
[0023] Figure 4 This is the Fourier transform infrared (FTIR) spectra of GO, GO-DA, GO-TiO2 and DA@GO-TiO2 in analysis example 2 of the present invention.
[0024] Figure 5 This is the Raman spectrum analysis diagram of GO, GO-DA, GO-TiO2 and DA@GO-TiO2 in Analysis Example 2 of the present invention.
[0025] Figure 6 This is the Tafel curve diagram of GO, GO-DA, GO-TiO2 and DA@GO-TiO2 in analysis example 3 of the present invention.
[0026] Figure 7 The Tafel curves and corrosion current density diagrams of GO and DA@GO-TiO2 with different nano-titanium dioxide loadings in Analysis Example 4 of the present invention.
[0027] Figure 8 The four samples of GO, DA@GO-TiO2 / 0.1, DA@GO-TiO2 / 0.75, and DA@GO-TiO2 / 2.0 in the analysis example 4 of the present invention were subjected to EIS test to obtain Nyquist and Bode plots, where: Figure 8 (a) Nyquist plot of GO and modified graphene oxide loaded with different amounts of nano-TiO2. Figure 8 (b) is the Nyquist plot of GO and modified graphene oxide loaded with different amounts of nano-TiO2 in the high-frequency region. Figure 8 (c) Bode impedance of GO and modified graphene oxide loaded with different amounts of nano-TiO2. Figure 8 (d) is the Bode phase angle diagram of GO and modified graphene oxide loaded with different amounts of nano-TiO2, where Figure 8 The inset in (d) is the equivalent circuit model.
[0028] Fig. 9 The thermogravimetric analysis (TGA) diagram of GO and DA@GO-TiO2 with different nano-titanium dioxide loadings in the analysis example 5 of the present invention is shown in FIG. Fig. 9 (a) is the TG graph of GO and modified graphene oxide loaded with different amounts of nano-TiO2. Fig. 9 (b) DTA diagram of modified graphene oxide loaded with different amounts of nano-TiO2. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Furthermore, the technical solutions between the various embodiments of the present invention may be combined with each other, but this must be based on the fact that they can be implemented by ordinary technicians in the field. When the combination of technical solutions is mutually contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0031] When numerical ranges are given in the embodiments, it should be understood that unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any method, device and material of the prior art similar or equivalent to the method, device and material in the embodiments of the present invention can also be used to implement the present invention.
[0032] Graphene oxide (GO) is a commonly used anti-corrosion material. It can be directly used as a coating for the anti-corrosion of metal materials, and can also be added to resin materials to improve the corrosion resistance of resin coatings. However, the surface of GO contains a large number of oxygen-containing functional groups, which make the GO nanosheets have strong interactions, such as π-π stacking, hydrogen bonding and van der Waals forces. These forces will cause GO nanosheets to agglomerate, thereby affecting the uniformity of GO dispersion and reducing corrosion resistance.
[0033] Doping with nano oxide particles is an effective method to improve the corrosion resistance of graphene oxide. Nanoparticles such as nano TiO2 can form bonds with oxygen-containing functional groups on the surface of GO, reducing the π-π stacking and agglomeration between GO sheets, which can not only improve the corrosion resistance of GO, but also enhance its mechanical strength and thermal stability. In addition, fully and evenly mixing the nanoparticles with GO and avoiding agglomeration of the nanoparticles during the mixing process are also the key to ensuring the corrosion resistance of the GO coating. The applicant found that adding suitable additives during the mixing process can ensure that the nanoparticles are fully dispersed in GO. For example, dopamine, as an organic substance with self-polymerization properties, can form a polydopamine film with super strong adhesion, thereby improving the binding ability of metal oxide nanoparticles with GO.
[0034] Based on the above, the present application uses dopamine to modify the GO surface, and then grafts nano-TiO2 onto the GO surface to synthesize the new material DA@GO-TiO2, and studies the effect of this method on the thermal stability of GO; at the same time, a DA@GO-TiO2 coating is prepared, and its corrosion resistance is studied by Tafel curve and electrochemical impedance spectroscopy (EIS), and it is concluded that the corrosion resistance and thermal stability of the modified graphene oxide obtained by the present application using dopamine and nano-TiO2 are greatly improved.
[0035] In the modified graphene oxide provided by the present invention, the graphene oxide presents a wrinkled layered structure, nano-titanium dioxide and dopamine are grafted on the surface of the graphene oxide, and a strongly adhesive polydopamine film and uniformly dispersed nano-titanium dioxide are formed on the surface of the graphene oxide.
[0036] The corrosion current density of the modified graphene oxide is 1.04×10 -5 ~2.09×10 -5 A / cm 2 .
[0037] The corrosion current density index comes from the corrosion resistance test. In a 3.5% NaCl solution, the electrochemical impedance spectroscopy (EIS) and Tafel curve test were performed on the samples at the OCP using a saturated Ag / AgCl electrode to detect the corrosion resistance of the samples. For the anodic reaction, the more positive the corrosion potential, the smaller the corrosion current density and the larger the polarization resistance, the better the corrosion resistance.
[0038] As shown in Table 1, the corrosion resistance of graphene oxide is different when it is loaded with different amounts of nano-titanium dioxide.
[0039] When the mass ratio of graphene oxide to nano-titanium dioxide is 1:0.25, the current density is 2.09×10 -5 A / cm 2 ;
[0040] When the mass ratio of graphene oxide to nano-titanium dioxide is 1:0.5, the current density is 1.92×10 -5 A / cm 2 ;
[0041] When the mass ratio of graphene oxide to nano-titanium dioxide is 1:0.75, the current density is 1.04×10 -5 A / cm 2 ;
[0042] When the mass ratio of graphene oxide to nano-titanium dioxide is 1:1.0, the current density is 2.02×10 -5 A / cm 2 ;
[0043] When the mass ratio of graphene oxide to nano-titanium dioxide is 1:1.5, the current density is 2.14×10 -5 A / cm 2 ;
[0044] When the mass ratio of graphene oxide to nano-titanium dioxide is 1:2.0, the current density is 2.33×10 -5 A / cm 2 ;
[0045] In some embodiments, when the mass ratio of graphene oxide to nano-titanium dioxide is 1:0.25-2.0, the corrosion current density of the modified graphene oxide is 1.04×10 -5 ~2.09×10 -5 A / cm 2 In some specific embodiments, when the mass ratio of graphene oxide to nano-titanium dioxide is 1:0.25-1.5, the corrosion current density of the modified graphene oxide is 1.04×10 -5 ~2.14×10 -5 A / cm 2 In some specific embodiments, when the mass ratio of graphene oxide to nano-titanium dioxide is 1:0.25-1.0, the corrosion current density of the modified graphene oxide is 1.04×10 -5 ~2.09×10 -5 A / cm 2 In some specific embodiments, when the mass ratio of graphene oxide to nano-titanium dioxide is 1:0.5-1.0, the corrosion current density of the modified graphene oxide is 1.04×10 -5 ~2.02×10 -5 A / cm 2 In some more specific embodiments, when the mass ratio of graphene oxide to nano-titanium dioxide is 1:0.75, the corrosion current density of the modified graphene oxide is 1.04×10 -5 A / cm 2 .
[0046] That is, in some embodiments, the corrosion current density of the modified graphene oxide can be 1.04×10 -5 ~2.09×10 -5 A / cm 2 In some specific embodiments, the corrosion current density of the modified graphene oxide can be 1.04×10 -5 ~2.02×10 -5 A / cm 2 In some more specific embodiments, the corrosion current density of the modified graphene oxide can be 1.04×10-5 A / cm 2 .
[0047] The functional groups on the surface of the modified graphene oxide prepared by the invention include -OH, C=N, C=C, COC, Ti-O-Ti and Ti-OC.
[0048] The present invention provides a method for preparing the modified graphene oxide as described in any one of the above, comprising the steps of:
[0049] S1. The graphene oxide is dispersed to obtain a graphene oxide dispersion.
[0050] In some embodiments, the dispersion treatment includes the steps of placing the graphene oxide in deionized water and ultrasonically dispersing for 30 to 60 minutes to obtain the graphene dispersion.
[0051] Specifically, graphene oxide can be placed in deionized water and ultrasonically dispersed for 30 minutes to obtain the graphene dispersion.
[0052] S2. The graphene oxide dispersion is mixed with dopamine hydrochloride and nano-titanium dioxide to obtain a graphene oxide mixture, and the graphene oxide mixture is stirred and solid-liquid separated in sequence, and the solid product is collected to obtain the modified graphene oxide, wherein the mass ratio of the graphene oxide to the dopamine hydrochloride and the nano-titanium dioxide is 1:0.25~2.0:0.25~2.0.
[0053] In some embodiments, the mass ratio of the graphene oxide to the dopamine hydrochloride and the nano-titanium dioxide can be 1:1:0.25-2.0. In some specific embodiments, the mass ratio of the graphene oxide to the dopamine hydrochloride and the nano-titanium dioxide can be 1g:1g:0.5-1.0g.
[0054] The step of successively subjecting the graphene oxide mixture to stirring treatment and solid-liquid separation, collecting the solid product, and obtaining the modified graphene oxide also includes washing the solid product with deionized water and ethanol alternately for 2 to 5 times, and drying the solid product to obtain the modified graphene oxide, wherein the drying treatment temperature is 50 to 70° C., and the drying treatment time is 10 to 20 hours.
[0055] The stirring treatment comprises: subjecting the graphene oxide mixture to ultrasonic treatment for 30 to 60 minutes, and then stirring at a rotation speed of 300 to 400 for 20 to 30 hours.
[0056] In some specific embodiments, the stirring treatment includes ultrasonicating the graphene oxide mixture for 30 to 60 minutes and then stirring at a rotation speed of 300 to 400 for 20 to 30 hours.
[0057] Methods for solid-liquid separation include filtration.
[0058] The temperature of the drying treatment may be 60° C., the duration of the drying treatment may be 12 h, and the means of the drying treatment may be vacuum drying.
[0059] The present invention also provides a modified graphene oxide coating solution, which is prepared from the modified graphene oxide described in any one of the above.
[0060] For example, a modified graphene oxide coating solution can be prepared using a perfluorosulfonic acid polymer solution as a binder, and the coating solution can be applied to the surface of a metal material to obtain a metal anti-corrosion coating.
[0061] The present invention also provides an application of the modified graphene oxide coating as described above in metal corrosion protection.
[0062] In order to facilitate those skilled in the art to further understand the present invention, examples are given below:
[0063] The raw materials used in the examples and comparative examples of the present invention are as follows. It is worth noting that the sources of the raw materials used in the present invention include but are not limited to the following:
[0064] Graphene oxide (GO) was commercial graphene oxide, dopamine hydrochloride (DA), nano-TiO2, NaCl, and Nafion solution were all analytically pure. Nano-TiO2 was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., dopamine hydrochloride (DA) NaCl, and Nafion solution were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., and carbon fiber paper was produced by SGL, Germany.
[0065] The characterization analysis used in the analysis examples of the present invention is as follows:
[0066] The surface morphology of the samples was observed by field emission scanning electron microscopy (SEM, JEOL JSM-6360LV); the crystal structure of the samples in the range of 5-90° (2θ) was analyzed by X-ray diffraction (XRD, Empyrean 2); Raman spectroscopy (Raman, Renishaw-inVia) was performed using a 532nm excitation laser source with an output power of 0.5mW and an acquisition time of 40s; the samples were measured by a NicoletIS10 Fourier transform infrared spectrometer (FTIR) in the range of 4000-500cm -1 The infrared spectrum in the range of 2000℃ was used; the microstructure and crystal structure of the samples were observed by transmission electron microscope (TEM) of JEOL JEM-F200 from Japan; the thermal stability changes of the samples at 30~800℃ were analyzed by thermogravimetric analysis (TGA, TA TGA-550).
[0067] Example 1 Preparation of modified graphene oxide
[0068] Weigh 1 g of graphene oxide in 50 mL of deionized water and disperse it by ultrasonic for 30 min to obtain a graphene oxide dispersion;
[0069] Then add 1g of dopamine hydrochloride and an appropriate amount of nano-TiO2 to the graphene oxide dispersion to obtain a graphene oxide mixture; the graphene oxide mixture continues to be ultrasonicated for 30 minutes, and then mechanically stirred at 350r / min at room temperature for 24 hours. After stirring, it is filtered and the solid product is washed alternately with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours to obtain modified graphene oxide, named DA@GO-TiO2.
[0070] When the amount of nano-titanium dioxide added was 0.1 g, DA@GO-TiO2 / 0.1 was obtained;
[0071] When the amount of nano-titanium dioxide added was 0.25 g, DA@GO-TiO2 / 0.25 was obtained;
[0072] When the amount of nano-titanium dioxide added was 0.5 g, DA@GO-TiO2 / 0.5 was obtained;
[0073] When the amount of nano-titanium dioxide added was 0.75 g, DA@GO-TiO2 / 0.75 was obtained;
[0074] When the amount of nano-titanium dioxide added was 1.0 g, DA@GO-TiO2 / 1.0 was obtained;
[0075] When the amount of nano-titanium dioxide added was 1.5 g, DA@GO-TiO2 / 1.5 was obtained;
[0076] When the amount of nano-titanium dioxide added was 2.0 g, DA@GO-TiO2 / 2.0 was obtained.
[0077] Comparative Example 1: Preparation of dopamine-modified graphene oxide
[0078] Weigh 1 g of graphene oxide in 50 mL of deionized water and disperse it by ultrasonic for 30 min to obtain a graphene oxide dispersion;
[0079] Then add 1 g of dopamine hydrochloride to the graphene oxide dispersion to obtain a graphene oxide mixture; continue to ultrasonicate the graphene oxide mixture for 30 minutes, and then mechanically stir at 350 r / min at room temperature for 24 hours. After the stirring is completed, it is filtered and the solid product is washed alternately with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours to obtain dopamine-modified graphene oxide, named GO-DA.
[0080] Comparative Example 2 Preparation of Titanium Dioxide Modified Graphene Oxide
[0081] Weigh 1 g of graphene oxide in 50 mL of deionized water and disperse it by ultrasonic for 30 min to obtain a graphene oxide dispersion;
[0082] Then add 0.1-0.25g of nano titanium dioxide to the graphene oxide dispersion to obtain a graphene oxide mixture; the graphene oxide mixture continues to be ultrasonicated for 30 minutes, and then mechanically stirred at 350r / min at room temperature for 24 hours. After the stirring is completed, it is filtered and the solid product is washed alternately with deionized water and ethanol several times, and vacuum dried at 60°C for 12 hours to obtain titanium dioxide modified graphene oxide, named GO-TiO2.
[0083] The following graphene oxide composite materials include GO, GO-DA, GO-TiO2 and DA@GO-TiO2 generated by adding different amounts of nano-titanium dioxide in Example 1. GO, GO-DA, GO-TiO2 and DA@GO-TiO2 generated by adding different amounts of nano-titanium dioxide in Example 1 mentioned in the analysis example are all prepared from Example 1 and Comparative Examples 1 to 2.
[0084] Analysis Example 1: Exploring the morphology and structure of various graphene oxide composite materials
[0085] The morphology and structure of GO, GO-DA, GO-TiO2 and DA@GO-TiO2 were observed by scanning electron microscopy (SEM). Figure 1 As shown, Figure 1 (a) to (d) are SEM images of GO, GO-DA, GO-TiO2 and DA@GO-TiO2 composite materials. Figure 1 As shown in (a) to (b), the graphene oxide before and after dopamine treatment showed obvious layered structures and stacked together, and the wrinkles on the surface were clearly visible. Figure 1 As shown in (c) to (d), both GO-TiO2 and DA@GO-TiO2 have granular substances distributed on their surfaces, indicating that nano-TiO2 is successfully loaded on the surface of graphene oxide. In addition, the nano-TiO2 on the surface of GO-TiO2 is seriously aggregated on the GO surface, while the nano-TiO2 on the surface of DA@GO-TiO2 is more evenly dispersed.
[0086] The microstructures of GO and DA@GO-TiO2 were observed by transmission electron microscopy (TEM). Figure 2 (a)-(d), where Figure 2 (a) is the TEM image of GO. Figure 2(b)-(d) are TEM images of DA@GO-TiO2 at different scales. Figure a shows a wrinkled graphene oxide sheet, which clearly presents a layered structure. Figure b shows a large amount of granular material distributed on the surface of GO, confirming that nano-TiO2 is successfully loaded on the surface of graphene oxide and is evenly dispersed without serious agglomeration. As can be seen from Figure c, nano-TiO2 can be loaded on the surface, edge of the sheet, and between the sheets of GO. Figure d clearly shows the amorphous region of graphene oxide and the lattice distribution of nano-TiO2. The two are intertwined to show that nano-TiO2 is successfully loaded on graphene oxide.
[0087] Analysis Example 2: Exploring the surface functional groups of various graphene oxide composite materials
[0088] GO, GO-DA, GO-TiO2 and DA@GO-TiO2 were identified and detected by XRD. Figure 3 As shown in Figure 2, the diffraction peaks corresponding to GO are 11.56°(001) and 43.92°(100). After adding GO and nano-TiO2, the diffraction peaks (001) of GO-DA, GO-TiO2 and DA@GO-TiO2 shift to the left to 11.04°, 11.08° and 11°, respectively, indicating that the interlayer spacing of the composite graphene oxide increases.
[10] .
[0089] The appearance of the GO (100) diffraction peak is due to the incomplete oxidation of graphite. With the addition of DA and / or nano-TiO2, the intensity of the diffraction peak (100) of graphene oxide decreases, and the diffraction peak (100) of DA@GO-TiO2 completely disappears, indicating that the oxygen-containing functional groups on the GO surface are reduced, which is due to the successful grafting of DA and nano-TiO2 onto the GO surface. Moreover, the diffraction peaks of GO-TiO2 and DA@GO-TiO2 at 2θ=25.26°, 37.88°, 47.96°, 53.86°, 54.98°, 62.74°, 68.76°, 70.36°, 75.16° and 82.72° correspond to the (101), (004), (200), (105), (211), (204), (116), (220), (215) and (224) planes of anatase TiO2, respectively, which also indicates that nano-TiO2 in GO-TiO2 and DA@GO-TiO2 is successfully loaded on graphene oxide.
[0090] Fourier transform infrared spectroscopy (FTIR) was used to analyze the changes in surface groups during GO modification, such as Figure 4 As shown in the FTIR spectrum of GO, the -1 The broad peak at 1714 cm -1 and 1114cm -1The characteristic peaks at 1620 cm-1 belong to the stretching vibrations of C=O and COC, indicating that there are oxygen-containing functional groups such as hydroxyl and carboxyl on the surface of GO. -1 The peak at belongs to the stretching vibration of C=C, which represents the residual unoxidized graphite in graphene oxide.
[0091] Compared with the original GO, the C=O characteristic peaks of GO-DA and DA@GO-TiO2 almost disappeared, indicating that the modification process directly covered the C=O on the GO surface. -1 A new characteristic peak belonging to C=N appears at 600 cm, which confirms that the decrease and disappearance of the (100) diffraction peak in XRD is due to the successful grafting of DA and nano-TiO2 onto the GO surface. -1 A strong peak appears near the stretching vibration of Ti-O-Ti. The intensity of the characteristic peak of Ti-O-Ti of GO-TiO2 is obviously higher than that of DA@GO-TiO2. This is because the nano-TiO2 on the surface of GO-TiO2 agglomerates to form larger particles, which leads to a significant increase in the intensity of the characteristic peak of Ti-O-Ti. DA@GO-TiO2 also has a peak at 567cm -1 A peak appears at , which corresponds to Ti-OC. The characteristic peaks of -O and C-OH in DA@GO-TiO2 are weaker than those in GO-TiO2, which also shows that the nano-TiO2 on the surface of DA@GO-TiO2 is more evenly dispersed.
[0092] Raman spectroscopy was used to analyze the structural changes of GO during the modification process, such as Figure 5 All samples were detected at 1350 cm -1 and 1590cm -1 Two obvious characteristic peaks appear near the surface, corresponding to the D peak and the G peak. The D peak is called the defect peak, which is related to the defects of the sp2 hybrid structure of carbon atoms and is related to the edges, vacancies and other defects of carbon atoms; the G peak originates from the in-plane vibration of the sp2 hybrid of carbon atoms, corresponding to the E2 photon mode in the center of the Brillouin zone, and represents the order of carbon atoms in GO.
[15] Therefore, the intensity ratio of the D peak to the G peak (ID / IG) is often used to measure the defects and disorder of graphene oxide. Through fitting calculations, the ID / IG values of GO, GO-PDA, GO-TiO2 and DA@GO-TiO2 are 1.587, 1.561, 1.213 and 1.497, respectively. The ID / IG value of GO-TiO2 is significantly smaller than that of the other three samples. This is because the highly crystalline TiO2 agglomerates in GO. After adding DA, the ID / IG ratio of DA@GO-TiO2 is significantly restored, indicating that DA promotes the dispersion of TiO2.
[0093] Analysis Example 3: Investigation of the Corrosion Resistance of Various Graphene Oxide Composite Materials
[0094] In 3.5% NaCl solution, electrochemical impedance spectroscopy (EIS) and Tafel curve tests were performed on the samples at OCP using a saturated Ag / AgCl electrode to detect the corrosion resistance of the samples. 2 The working electrode was placed in the electrolyte, and the Tafel polarization of each graphene oxide composite material sample was performed in the range of ±0.8V at the open circuit voltage (OCP). The Tafel curves of different samples were obtained as shown in Figure 6 shown.
[0095] The anode slope (b a ), cathode slope (b c ), corrosion potential (E corr ), corrosion current density (I corr ) and polarization resistance (R p ) and other parameters, as shown in Table 1. Among them, the anode slope (b a ), cathode slope (b c ) and corrosion current (I corr ) is obtained by extrapolation, the polarization resistance (R p ) is calculated by the following formula:
[0096]
[0097] Among them, b a is the anode slope, b c is the cathode slope, I corr is the corrosion current density. For the anodic reaction, E corr The more positive, I corr The smaller, R p The larger the value, the better the corrosion resistance.
[0098] The Tafel curves of GO, GO-DA, GO-TiO2 and DA@GO-TiO2 are shown in Figure 2. Figure 6As shown. Compared with the original GO, the corrosion potential of GO-DA and GO-TiO2 is higher, indicating that they have better thermodynamic stability and are less likely to form corrosion. However, from a kinetic point of view, as the anodic potential increases, the corrosion current density of GO-DA and GO-TiO2 quickly exceeds that of GO, indicating that their corrosion rate is faster. Therefore, the corrosion resistance of GO-DA and GO-TiO2 is weaker than that of GO. On the contrary, the corrosion potential of DA@GO-TiO2 increases significantly, and the corrosion current density is smaller than that of GO, indicating that the corrosion resistance of the material can be improved by treating it with DA and TiO2 at the same time. The reason is that DA dissolves in water and polymerizes to form polydopamine (PDA) wrapped on the surface of GO. PDA has adhesion, which can make nano-TiO2 disperse evenly on the surface of GO and prevent agglomeration. The passivation film on the surface of nano-TiO2 improves the density and barrier properties of the material. Therefore, DA@GO-TiO2 has the best corrosion resistance.
[0099] Analysis Example 4: Study on the Corrosion Resistance of Modified Graphene Oxide with Different Nano-TiO2 Particle Loading Amounts
[0100] like Figure 7 (a) to (b) and Table 1, where Figure 7 (a) and Figure 7 (b) The Tafel curve and corrosion current density of modified graphene oxide with different nano-titanium dioxide particle loadings. When the TiO2 addition amount is 0.1g, the corrosion potential and polarization resistance are lower than those of the original GO, and the corrosion current density is also higher, indicating that the corrosion resistance is reduced. This is due to the uneven distribution of nano-TiO2 in the graphene oxide matrix. As the TiO2 addition amount continues to increase, the corrosion potential moves to a positive value, and I corr The value decreases, indicating that the inertness of the material increases and the corrosion resistance is improved. When the TiO2 addition amount is 0.75g, the corrosion resistance of GO-TiO2 / 0.75 is the best, with a corrosion potential of -0.278V and a corrosion current density of 1.04×10 -5 A / cm 2 , polarization resistance is 2533Ω / cm 2 . However, when TiO2 was further added to 2g, the corrosion current density of the GO coating increased and the polarization resistance decreased, indicating that the corrosion resistance decreased. The reason is that adding an appropriate amount of nano-TiO2 can increase the barrier properties of the material. At the same time, the surface oxide film of TiO2 is further thickened under the condition of applying an anodic potential, thereby improving the corrosion resistance of the material. Adding excessive nano-TiO2 can easily cause the sample after ultrasonic dispersion to agglomerate again, making the graphene oxide and nano-TiO2 mixed unevenly, resulting in granular deposition, which leads to a decrease in the corrosion resistance of the material.
[0101] Table 1 Tafel curve fitting parameters of various graphene oxide composites
[0102]
[0103] EIS tests were performed on four samples, including GO, DA@GO-TiO2 / 0.1, DA@GO-TiO2 / 0.75, and DA@GO-TiO2 / 2.0, to obtain Nyquist and Bode plots with a frequency range of 10 5 Hz~10 -2 Hz, the sine amplitude is 5mV, such as Figure 8 As shown, Figure 8 (a) Nyquist plot of GO and modified graphene oxide loaded with different amounts of nano-TiO2. Figure 8 (b) is the Nyquist plot of GO and modified graphene oxide loaded with different amounts of nano-TiO2 in the high-frequency region. Figure 8 (c) Bode impedance of GO and modified graphene oxide loaded with different amounts of nano-TiO2. Figure 8 (d) is the Bode phase angle diagram of GO and modified graphene oxide loaded with different amounts of nano-TiO2, where Figure 8 The inset in (d) is the equivalent circuit model.
[0104] The Nyquist plot is in the shape of an arc, and the radius of curvature of the arc corresponding to DA@GO-TiO2 / 0.75 is larger, indicating that the impedance of charge transfer during the reaction is greater. Figure 8 (c)- Figure 8 (d) As shown in the Bode diagram, the impedance modulus of DA@GO-TiO2 / 0.75 in the low-frequency region is higher than that of other samples, indicating that it has a higher barrier ability to the penetration of corrosive media, thereby more effectively slowing down the corrosion process. The maximum phase angle of DA@GO-TiO2 / 0.75 is about 77°, which is higher than that of other samples, indicating that it has better surface uniformity. In the phase angle diagram, DA@GO-TiO2 / 0.1, DA@GO-TiO2 / 0.75 and DA@GO-TiO2 / 2.0 have two peaks at high and low frequencies. The Nyquist diagram also shows that these three samples have two arcs with different curvature radii. This is because the passivation film on the TiO2 surface hinders electron transfer and increases the impedance value.
[0105] The EIS test results of different samples were fitted and the fitted equivalent circuit (EEC) was inserted into Figure 8 In (d), the EEC consists of a 2RC circuit, where R s Represents the solution resistance, which is determined by the distance between the working electrode and the reference electrode, R c and R ctrepresent the GO coating resistance and charge transfer resistance respectively. The corrosion resistance of the sample is represented by R c and R ct The interface capacitance cannot be represented by an ideal capacitance element, and the constant phase angle element CPE can better reflect the actual situation. Its impedance is determined by the following formula:
[0106] Z CPE =Y -1 jω -n
[0107] Among them, Y is the CPE power parameter, j is an imaginary constant ω is the angular frequency, and n is the CPE index, which represents the deviation of CPE from the ideal capacitance (n=0 is ideal resistance, n=1 is ideal capacitance, and n=0.5 is Warburg impedance).
[0108] The parameters obtained after EIS data fitting are shown in Table 2. It can be seen that after adding nano-TiO2, the coating resistance R c The value of DA@GO-TiO2 / 0.75 is significantly increased, indicating that the sample has improved its barrier ability to ion penetration. c and R ct The values of DA@GO-TiO2 / 0.1 are significantly larger than those of other samples, indicating that it has the best barrier performance and the charge transfer process on the electrode surface is most hindered, so the corrosion reaction rate is the lowest. c +R ct The value is the smallest, indicating that its corrosion resistance is the worst, which is consistent with the results of Tafel curve analysis. In addition, compared with the original GO, after adding an appropriate amount of nano-TiO2, the double-layer capacitance of the sample decreases, indicating that there are fewer active sites on the electrode surface and the charge transfer rate is slower. This is because the incorporation of nano-TiO2 generates a passivation film on the electrode surface, which reduces the charge exchange between the electrode and the electrolyte, resulting in a slower electrode reaction rate, thus making it have better corrosion resistance. The double-layer capacitance value of DA@GO-TiO2 / 0.75 is the lowest, indicating that it has the best corrosion resistance.
[0109] Table 2 EIS fitting parameters
[0110]
[0111] Analysis Example 5: Study on the thermal stability of modified graphene oxide with different nano-titanium dioxide particle loadings
[0112] Thermogravimetric analysis (TGA) of the samples was performed at a rate of 10°C / min from 30°C to 800°C under N2 atmosphere. Fig. 9 As shown, Fig. 9 (a) is the TG graph of GO and modified graphene oxide loaded with different amounts of nano-TiO2. Fig. 9 (b) is the DTA graph of GO and modified graphene oxide loaded with different amounts of nano-TiO2. The weight loss before 100°C represents the loss of water in graphene oxide. The weight of all samples dropped sharply between 100 and 300°C, representing the thermal decomposition of oxygen-containing functional groups in graphene oxide. Between 150 and 250°C, GO lost 28% of its weight, while DA@GO-TiO2 / 0.1, DA@GO-TiO2 / 0.5, DA@GO-TiO2 / 0.75 and DA@GO-TiO2 / 2.0 lost 20%, 13%, 15% and 8% of their weight, respectively, which is significantly reduced compared to GO, indicating that the modification method can prevent the thermal decomposition of oxygen-containing functional groups on the surface of GO, thereby improving its thermal stability. In addition, it can be seen from the figure that all samples slowly lose weight at 300-800℃. The weight loss in this stage is caused by the decomposition of the carbon skeleton. At 800℃, GO only has 33.3% of its weight left, while the remaining weights of DA@GO-TiO2 / 0.5, DA@GO-TiO2 / 0.75 and DA@GO-TiO2 / 2.0 are 59.47%, 62.72% and 72.65% respectively, which are significantly higher than GO, indicating that the addition of TiO2 can improve the thermal stability of GO. Fig. 9 (b) It can be seen that the weight loss peak of GO is at 183°C, while the weight loss peaks of other samples doped with nano-TiO2 are all greater than 220°C, and the weight loss peak of DA@GO-TiO2 / 0.75 is the highest, located at 236°C, proving that the improvement of the thermal stability of GO by DA and TiO2 modification is related to the amount of nano-TiO2 added.
[0113] in conclusion
[0114] The present invention prepares a novel graphene oxide composite material using dopamine grafting and nano-TiO2 modification, and observes and explores the surface morphology and microstructure of DA@GO-TiO2 using scanning electron microscopy, transmission electron microscopy, XRD, FTIR and Raman spectroscopy. The corrosion resistance of the GO coating when dopamine and nano-TiO2 are separately and simultaneously added is explored using Tafel curve and EIS test, and the effect of the amount of nano-TiO2 added on the corrosion resistance and thermal stability of GO is explored. The results show that the corrosion resistance of the GO coating is the best when dopamine and nano-TiO2 are added simultaneously, because the adhesive polydopamine generated by dopamine self-polymerization is wrapped on the GO surface, making the nano-TiO2 more evenly dispersed on the GO surface, and the TiO2 surface passivation film increases the barrier property of the material, thereby greatly improving the corrosion resistance of the material. In addition, when the amount of nano-TiO2 added is too little or too much, the corrosion resistance of the coating will decrease. When the amount of nano-TiO2 added is 0.75g, the GO coating has the best corrosion resistance. At this time, the nano-TiO2 will not be unevenly distributed on the GO surface, nor will it agglomerate due to excessive addition. TGA results show that the more nano-TiO2 is added, the better the thermal stability of GO. The weight loss peak position of DA@GO-TiO2 / 0.75 is the highest, which not only greatly improves the thermal stability of GO, but also maintains the best corrosion resistance, providing a reference for improving the corrosion resistance and thermal stability of GO materials at the same time.
[0115] The above technical solutions of the present invention are only preferred embodiments of the present invention, and the patent scope of the present invention is not limited thereto. All equivalent structural changes made by using the contents of the present invention specification and drawings under the technical concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A modified graphene oxide, characterized in that: The invention comprises graphene oxide, nano titanium dioxide and a polydopamine film, wherein the graphene oxide is in a wrinkled layered structure, the polydopamine film is wrapped on the surface of the graphene oxide, and the nano titanium dioxide is uniformly dispersed on the surface of the graphene oxide wrapped with the polydopamine film.
2. The modified graphene oxide according to claim 1, characterized in that The corrosion current density of the modified graphene oxide is 1.04×10 -5 ~2.33×10 -5 A / cm 2 .
3. The modified graphene oxide according to claim 1, characterized in that The functional groups on the surface of the modified graphene oxide include -OH, C=N, C=C, COC, Ti-O-Ti, and Ti-OC.
4. A method for preparing modified graphene oxide according to any one of claims 1 to 3, characterized in that: Includes steps: The graphene oxide is dispersed to obtain a graphene oxide dispersion; The graphene oxide dispersion is mixed with dopamine hydrochloride and nano-titanium dioxide to obtain a graphene oxide mixture, and the graphene oxide mixture is subjected to stirring treatment and solid-liquid separation in sequence, and the solid product is collected to obtain the modified graphene oxide, wherein the mass ratio of the graphene oxide to the dopamine hydrochloride and the nano-titanium dioxide is 1:0.25-2.0:0.25-2.
0.
5. The method for preparing modified graphene oxide according to claim 4, characterized in that: The mass ratio of the graphene oxide to the dopamine hydrochloride and the nano titanium dioxide is 1:1:0.5-1.
0.
6. The method for preparing modified graphene oxide according to claim 4, characterized in that: The dispersion treatment comprises the steps of placing the graphene oxide in deionized water and performing ultrasonic dispersion for 30 to 60 minutes to obtain the graphene dispersion.
7. The method for preparing modified graphene oxide according to claim 4, characterized in that: The stirring treatment comprises: subjecting the graphene oxide mixture to ultrasonic treatment for 30 to 60 minutes, and then stirring at a rotation speed of 300 to 400 for 20 to 30 hours.
8. The method for preparing modified graphene oxide according to claim 7, characterized in that: The step of successively subjecting the graphene oxide mixture to stirring treatment and solid-liquid separation, collecting the solid product, and obtaining the modified graphene oxide also includes washing the solid product with deionized water and ethanol alternately for 2 to 5 times, and drying the solid product to obtain the modified graphene oxide, wherein the drying treatment temperature is 50 to 70° C., and the drying treatment time is 10 to 20 hours.
9. Use of the modified graphene oxide as claimed in any one of claims 4 to 8 in metal corrosion protection.
10. A modified graphene oxide coating solution, characterized in that: It comprises the modified graphene oxide as described in any one of claims 4 to 8 and a binder.
Citation Information
Patent Citations
Ultraviolet-reducible graphene oxide complex material and preparation method thereof
CN109485850A
Preparation method and application of modified anti-corrosion super-hydrophobic integrated coating
CN112300697A
Modified graphene oxide, water-based anticorrosive coating and preparation method of modified graphene oxide and water-based anticorrosive coating
CN113755036A
Graphene oxide / polyaniline / titanium dioxide ternary nano composite material, anticorrosive coating material and preparation method
CN113773643A
Application of graphene oxide titanium dioxide composite material and anti-corrosion coating
CN113881266A